I Have Lost My Way - Forman, Gayle (New York Viking, an imprint of Penguin Random House LLC, 2018)
"Three teengers, Freya, Harun, and Nathaniel feel lost in various ways and when they collide in Central Park, they begin to find purpose in their lives"--
Keywords: Friendship -- Juvenile fiction; Teenagers -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Self-actualization (Psychology) -- Juvenile fiction; Loss (Psychology) -- Juvenile fiction; Friendship -- Fiction; Teenagers -- Fiction; Interpersonal relations -- Fiction; Self-actualization (Psychology) -- Fiction; Loss (Psychology) -- Fiction; Central Park (New York, N.Y.) -- Juvenile fiction; New York (N.Y.) -- Juvenile fiction; Central Park (New York, N.Y.) -- Fiction; New York (N.Y.) -- Fiction